2015
DOI: 10.1039/c5sm00658a
|View full text |Cite
|
Sign up to set email alerts
|

Gemini supra-amphiphiles with finely-controlled self-assemblies

Abstract: Novel gemini supra-amphiphiles, [Mim-4-Mim][DBS](2) and [Mim-4-Mim][DS](2), were facilely constructed. A slight variation of building blocks can effectively modulate the driving forces for the fabrication of gemini supra-amphiphiles, thus leading to the fine control of subsequent self-assemblies. [Mim-4-Mim][DS](2), constructed via electrostatic attraction, tends to form micelles and hexagonal liquid crystals. Rich lamellar structures, including unilamellar and multilamellar vesicles, planar bilayers, and lame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…In the light of the literature reports which state that the smaller nanoparticles in the range of 8-20 nm not only can easily penetrate the deep regions of interstitial tissue, but also circumvent the rapid renal clearance of the drugs being delivered, 46 it seemed that the size of the selfassembled system was quite appropriate for transport purposes. The estimated assembly dimensions of the dominating nanosized species in the aqueous solution ranged from 6-19 nm and followed the order: mPEG-550; C-10 chain (20) < mPEG-1000; C-10 chain (21) < mPEG-1000; C-18 chain (22).…”
Section: Physico-chemical Characterization Of Supramolecular Nanostrumentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the literature reports which state that the smaller nanoparticles in the range of 8-20 nm not only can easily penetrate the deep regions of interstitial tissue, but also circumvent the rapid renal clearance of the drugs being delivered, 46 it seemed that the size of the selfassembled system was quite appropriate for transport purposes. The estimated assembly dimensions of the dominating nanosized species in the aqueous solution ranged from 6-19 nm and followed the order: mPEG-550; C-10 chain (20) < mPEG-1000; C-10 chain (21) < mPEG-1000; C-18 chain (22).…”
Section: Physico-chemical Characterization Of Supramolecular Nanostrumentioning
confidence: 99%
“…11,20 Gemini surfactants, characterized by the presence of two hydrophilic head groups and two hydrophobic tails, linked by a rigid or exible spacer, holds unique properties and rich self-assembly behaviour, as a result of which they have gained considerable attention. 21,22 Fabricating these dimeric or twin amphiphiles confers them superior physico-chemical properties compared to the conventional monomeric surfactants e.g. low critical micellar concentration (CMC) as a consequence of the presence of two hydrophobic tails, high surface activity, high solubilization capacity, low Kra temperature, unusual rheological properties, multiple aggregate morphologies, high wetting ability etc.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with conventional amphiphiles, there appears an emerging field of supra‐amphiphiles, which refer to amphiphiles fabricated on the basis of various noncovalent interactions and/or dynamic covalent bonds, such as host‐guest interaction, electrostatic interaction, charge‐transfer interaction, hydrogen bond, coordination bond, imine bond and boronic ester bond . Generally, the strategies for designing supra‐amphiphiles can be sorted into two main categories .…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made by several researchers to theoretically interpret interactions in mixed systems [18]. Sophisticated mixed multiple systems containing multi-hydrophilic head groups have attracted much attention [19][20][21][22][23][24]. We explored the synergistic action of surfactants and we found that the AETAS had a good synergy effect with natural surfactants.…”
Section: Introductionmentioning
confidence: 97%